Studi Literatur Tentang Program Pump System Improvement Modeling Tool Untuk Penyempurnaan Kinerja Sistem Pompa - Sukamta, Sukamta; Husda, Syamsul Muarif; Caroko, Novi (Universitas Muhammadiyah Yogyakarta, 2017)
In the industrial world often encountered actual loads do not match the design load.Â These differences lead to energy wastage. Pumping system is one of the systems that always exist in the industry. Improving of pumping system performance is an important step in saving energy. Impeller trimming is one method to improve the performance of the pump system. One of the obstacles in performing the impeller trimming method is to determine the magnitude of the impeller diameter reduction to be performed. Currently, many software developed to improve the performance of pumps and pumping systems. One of the softwares is Pump System Improvement Modeling Tool (PSIM). Imprimer trimming method is one of the features in PSIM. To be optimal in the use of PSIM in the improvement of the pump system it is necessary to conduct a literature study on PSIM to improve the performance of the pump system. In this article has been studied PSIM literature on the process of perfection of centrifugal pump system with impeller trimmer method by taking case study on hot water provider system. The method used in this literature study is by comparing the results of PSIM calculations on case studies with the pump theory of the impeller trimming method. Through this comparison will be known the advantages of PSIM and weaknesses, PSIM calculation margin error compared to the theoretical calculations. By knowing these things then it can be determined the limits of the use of PSIM in the improvement of pump system performance. The result of analysis shows that PSIM trimming impeller calculation is based more on the calculation according to affinity law than any other theory, even in the calculation there is error margin. The tendency of data is the greater the value of the reduction the greater the deviation. If based on the theory then the calculation of PSIM which can be used as a guide in calculating the reduction of diameter is a maximum reduction of 15% or 85% of the original diameter. A larger reduction of the value needs to be re-measured to the characteristics of the pump system.